A study on the alteration tendency of physical ability index and stress feature index of elite female judoists in intensity training - Chen, M. (Modern Applied Science, 2008)
A cluster analysis was conducted to preliminarily screen the physical ability index and stress feature index from the hormones measured in this study, and the alterations of the indexes in intensity training of elite female judoists were discussed. Results showed that the intensity training affected alterations of physical ability indexes, including LH, TT, T/C and PRL, and the stress feature indexes, including EN, ACTH, ?-END and C. The results suggested that in intensity training, alterations of physical capacity were affected by several factors, such as endocrine indexes.